Coping behaviors to deal with stress and stressor consequences among construction professionals: A case study at the Gaza Strip, Palestine. Issue 1 (3rd April 2018) - Enshassi, Adnan; Al-Swaity, Eman; Abdul Aziz, Abdul Rashid; Choudhry, Rafiq
Abstract : Purpose: Construction experts face several types of stresses at construction sites. The purpose of this study is to recognize and investigate dominant coping behaviors to overcome stress among construction professionals at the Gaza Strip. Design/methodology/approach: For the purpose of this paper, a survey which used self-administrative questionnaires was conducted. A total of 320 questionnaires were distributed randomly to construction professionals working at the Gaza Strip. From the total questionnaires that were distributed, 183 were returned. This shows a 51 per cent response rate. Relative importance index and principal component analysis were applied to examine the responses. This study explored two central coping behaviors, namely, problem-focused and emotion-focused behaviors. Findings: In relation to the problem-focused behaviors, a factor analysis revealed three underlying factors, namely, planned and constructive review problem-solving, need for social contributory support and confronted coping mechanism. As for emotion-focused coping behavior strategy, three principal factors were identified and named in order of their significance. These three principal factors include accepting responsibility, avoidance and seeking emotional support. Originality/value: There is limited attention from researchers with regard to coping behaviors so as to deal with stress and stressors in the Palestinian construction industry. Therefore, this study aims to fill the gap for stress-related issues in the construction sector of Palestine. The outcomes of this study will be valuable for construction companies which pursue improvements in human resources, productivity and future strategy.